The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jphp.13111
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating suitability of the Caco-2 cell model for BCS-based biowaiver according to the recent FDA and ICH harmonised guidelines

Abstract: Objective According to the regulatory guidelines, one of the critical steps in using in‐vitro permeability methods for permeability classification is to demonstrate the suitability of the method. Here, suitability of the permeability method by using a monolayer of cultured epithelial cells was verified with different criteria. Methods Imaging with a transmission electron microscope was used for characterisation of the cells. Monolayer integrity was confirmed by transepithelial electrical resistance measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 75 publications
2
12
0
Order By: Relevance
“…This means that potential active transport in the intestine does not have any significant role in limiting desloratadine absorption. This is in line with our permeability data, since the efflux ratio is well below 2 even when measured by an in vitro model, which is known to over-express P-gp efflux transporter (21).…”
Section: In Vitro Permeability Of Desloratadine Through Caco-2 Monolasupporting
confidence: 91%
“…This means that potential active transport in the intestine does not have any significant role in limiting desloratadine absorption. This is in line with our permeability data, since the efflux ratio is well below 2 even when measured by an in vitro model, which is known to over-express P-gp efflux transporter (21).…”
Section: In Vitro Permeability Of Desloratadine Through Caco-2 Monolasupporting
confidence: 91%
“…The Caco-2 human colon adenocarcinoma line has been extensively used in biomedical studies and considered as a gold standard for estimating intestinal permeability of drugs in pharmaceutical validation over the past decades [5][6][7] . The Caco-2 epithelium demonstrates enterocyte-like phenotype with transcriptomic signatures of normal small intestinal epithelium when cultured for 3 weeks in a static condition despite its cancer origin [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Certain excipients reduce the GI transit period, therefore, GI transit period serves as a critical factor for bioequivalence proposing more strict criteria for dissolution to make sure complete dissolution in the stomach (Koch et al, 1993). Apart from in-vivo pharmacokinetic studies, presently only Caco-2 permeability studies are endorsed in the ICH harmonised guideline (ICH, 2018;Jarc et al, 2019). A study conducted to determine consequence of Caco-2 permeability for some formulation excipients showed that permeability across Caco-2 monolayers did not aggravate by such excipients (Rege et al, 2001).…”
Section: Technical Basis For Biowaiversmentioning
confidence: 99%